Genetic variants modify the associations of concentrations of methylmalonic acid, vitamin B-12, vitamin B-6, and folate with bone mineral density. Issue 2 (8th May 2021) - Liu, Ching-Ti; Karasik, David; Xu, Hanfei; Zhou, Yanhua; Broe, Kerry; Cupples, L Adrienne; Cpgm de Groot, Lisette; Ham, Annelies; Hannan, Marian T; Hsu, Yi-Hsiang; Jacques, Paul; McLean, Robert R; et al.
ABSTRACT: Background: Elevated plasma homocysteine has been found to be associated with an increased risk of osteoporosis, especially hip and vertebral fractures. The plasma concentration of homocysteine is dependent on the activities of several B vitamin–dependent enzymes, such as methylenetetrahydrofolate reductase (MTHFR), methionine synthase (MTR), methionine synthase reductase (MTRR), and cystathionine β-synthase ( CBS ). Objectives: We investigated whether genetic variants in some of the genes involved in 1 carbon metabolism modify the association of B vitamin–related measures with bone mineral density (BMD) and strength. Methods: We measured several B vitamins and biomarkers in participants of the Framingham Offspring Study, and performed analyses of methylmalonic acid (MMA) continuously and <210 nmol/L; pyridoxal-5'-phosphate; vitamin B-12 continuously and ≥258 pmol/L; and folate. The outcomes of interest included areal and volumetric BMD, measured by DXA and quantitative computed tomography (QCT), respectively. We evaluated associations between the bone measures and interactions of single nucleotide polymorphism with a B vitamin or biomarker in Framingham participants ( n  = 4310 for DXA and n  = 3127 for QCT). For analysis of DXA, we validated the association results in the B-PROOF cohort ( n  = 1072). Bonferroni-corrected locus-wide significant thresholds were defined to account for multiple testing. Results: The interactions between rs2274976 and vitamin B-12 and rs34671784 and MMA <210 nmol/L were associated with lumbar spine BMD, and the interaction between rs6586281 and vitamin B-12 ≥258 pmol/L was associated with femoral neck BMD. For QCT-derived traits, 62 interactions between genetic variants and B vitamins and biomarkers were identified. Conclusions: Some genetic variants in the 1-carbon methylation pathway modify the association of B vitamin and biomarker concentrations with bone density and strength.  These interactions require further replication and functional validation for a mechanistic understanding of the role of the 1-carbon metabolism pathway on BMD and risks of fracture.